Effect of membrane rigidification on the BrAFP1 expression and cold-tolerance in Brassica rapa - Dong, Xiaoyun; Wang, Jinxiong; Wei, Jiaping; Zheng, Guoqiang; Wu, Zefeng; Cui, Junmei; Yang, Xuezhen; Li, Baojin; Zhu, Shujun; Sa, Ermei; Yang, Fengpeng; Liu, Zigang (Frontiers in Plant Science, 2025)
IntroductionThe cold tolerance of winter rapeseed cultivars is critically important for winter survival and yield formation in northern area. BrAFP1, an antifreeze protein in Brassica rapa, is hypothesized to stabilize membranes and inhibit ice crystal formation.Methodswe cloned the BrAFP1 promoter from the cold-tolerant cultivar Longyou 7 (L7) and constructed the proBrAFP1::GUS expression vector to investigate the impact of membrane state changes on BrAFP1 expression and the cold tolerance in winter rapeseed. Ten independent transgenic T3 lines were generated, among which T3-5 and T3-7 were selected for subsequent analysis.ResultsThe dimethyl sulfoxide (DMSO) treatment in the absence of cold exposure activated the transcriptional activity of proBrAFP1, a cold-inducible promoter; in contrast, benzyl alcohol (BA) treatment eliminated its cold-induced activation. The expression levels of cold-responsive genes, including cyclic nucleotide-gated channel 1 (CNGC1), open stomata 1 (OST1), and inducer of CBF expression 1 (ICE1), as well as membrane fluidity-related genes, such as acyl-lipid desaturase 2 (ADS2), fatty acid desaturase 2 (FAD2), and sensitive to freezing 2 (SFR2), were significantly increased following DMSO pretreatment, while BA treatment significantly inhibited the expression of these genes. Furthermore, ABA and SA levels are closely linked to alterations in the membrane state, compared to untreated plants, the levels of ABA and SA in the leaves markedly increased at 4°C after DMSO and BA treatment but decreased at -4°C.ConclusionCollectively, DMSO pretreatment enhanced cold tolerance, while BA pretreatment improved cell survival under cold stress, which is important for practise of keeping the rapeseed yields.